Ethical values and the perception of corruption - Riccardo. Pelizzo; Meirat Omarov (Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of the present study is to assess the ethical standards of Indonesian parliamentarians, how they provides Indonesian MPs with proper cognitive guidance, to identify what factors may be responsible for variation in ethical standards and to assess how Indonesia parliamentarians compare to legislators and policy makers from other countries. The methodological approach, employed in each of these studies, to map the ethical preferences of parliamentarians can also be used to explore how the ethical world of Indonesian parliamentarians has changed over time, in addition to replicating the analyses performed in previous studies with a larger sample, the paper explored three sets of questions that previous studies had not addressed. First, we explored what are some of the correlates or some possible causes of individual attitudes; Second, we assessed how the ethical attitudes and standards of respondents shape the way they perceive corruption; Third, we performed a similar analysis with data collected among Kazakhstani civil servants to test whether the perception of corruption is influenced by ethical attitudes also outside Indonesia or not.